2017
DOI: 10.1038/s41598-017-15128-8
|View full text |Cite
|
Sign up to set email alerts
|

The lipid raft-dwelling protein US9 can be manipulated to target APP compartmentalization, APP processing, and neurodegenerative disease pathogenesis

Abstract: The trafficking behavior of the lipid raft-dwelling US9 protein from Herpes Simplex Virus strikingly overlaps with that of the amyloid precursor protein (APP). Both US9 and APP processing machinery rely on their ability to shuttle between endosomes and plasma membranes, as well as on their lateral accumulation in lipid rafts. Therefore, repurposing US9 to track/modify these molecular events represents a valid approach to investigate pathological states including Alzheimer’s disease and HIV-associated neurocogn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 66 publications
(73 reference statements)
0
6
0
1
Order By: Relevance
“…Studies in cell cultures, including primary neurons, demonstrated that after reaching the plasma membrane, US9 is recycled to endosomes [ 53 ], closely overlapping APP trafficking behavior. We also demonstrated that US9-driven TEV protease (TEV: tobacco etch virus) can cleave an APP-driven TEV protease reporter substrate, demonstrating that US9 can locate a functional cargo in close proximity of APP [ 39 ]. Building on these observations, we explored the possibility to use US9 to modulate APP processing without targeting endogenous enzymes.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Studies in cell cultures, including primary neurons, demonstrated that after reaching the plasma membrane, US9 is recycled to endosomes [ 53 ], closely overlapping APP trafficking behavior. We also demonstrated that US9-driven TEV protease (TEV: tobacco etch virus) can cleave an APP-driven TEV protease reporter substrate, demonstrating that US9 can locate a functional cargo in close proximity of APP [ 39 ]. Building on these observations, we explored the possibility to use US9 to modulate APP processing without targeting endogenous enzymes.…”
Section: Resultsmentioning
confidence: 99%
“…We recently discovered a remarkable overlap between the cellular trafficking of APP and US9 [39]. US9 is a protein necessary for α-herpesviruses anterograde transport in neurons [40][41][42][43].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Присутствие в МАМ пресенилинов и остатка C99 [68], который расщепляется γ-секретазой [69], может объяснить локализацию Aβ в митохондриях [50]. Кроме того, МАМ представляет собой липидный рафтподобный домен [70], а, как известно, расщепление АРР по амилоидогенному пути зависит от липидного рафтa [71,72]. Изменение активности γ-секретазы приводит к накоплению фрагмента C99 в МАМ, вызывая этерификацию холестерина и гидролиз сфинголипидов, а также митохондриальную дисфункцию [73].…”
Section: гибель нейронаunclassified
“…The presence of presenilins and the C99 fragment, which is cleaved by γ-secretase [ 69 ], in MAM [ 68 ] may explain the mito chondrial localization of Aβ [ 50 ]. In addition, MAM is a lipid raft-like domain [ 70 ], while APP cleavage via the amyloidogenic pathway depends on the lipid raft [ 71 , 72 ]. A change in γ-secretase activity leads to the accumulation of the C99 fragment in MAM, inducing esterification of cholesterol, hydrolysis of sphingolipids, and mitochondrial dysfunction [ 73 ].…”
Section: Pathways Of Aβ Intake By Mitochondria and Its Effect On Mito...mentioning
confidence: 99%